Pemahaman, Kesiapan dan Potensi Pemanfaatan Artificial Intelligence untuk Mendukung Pelayanan Kesehatan di Klinik Pratama - Nurhasmadiar Nandini; Rani Tiyas Budiyanti; Sutopo Patria Jati (Jurnal Manajemen Informasi dan Administrasi Kesehatan (JMIAK), 2026)
The use of Artificial Intelligence (AI) in healthcare facilities has begun to be implemented at both the hospital and primary healthcare facilities levels, although it is still limited and simple. This study aims to analyze the understanding of staff, the readiness of staff and organizations, and the potential use of AI to support healthcare services in primary clinics. This is a qualitative study conducted from March to October 2025 at two primary clinics in Semarang City. Informants in this study were clinic managers, doctors, and clinic administrators. Data collection was conducted through in-depth interviews with informants. Data analysis used content analysis techniques. The results show that the basic understanding of staff at the clinics is quite good, but detailed technical instructions and training are still needed. The clinics are quite ready in terms of infrastructure to support the use of AI. The potential for AI utilization is still vast, for example, for early detection, patient education, and other health and support services, if detailed guidelines and limitations are in place to ensure quality and safe healthcare. Staff at primary clinics have begun to utilize AI in several aspects, but still need expansion and more in-depth training to optimize the use of AI to provide effective, efficient, and safe healthcare.